2019
DOI: 10.1155/2019/7453169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synthetic Food Colours in Selected Confectioneries and Beverages in Jaffna District, Sri Lanka

Abstract: Colour is a key component to enhance the ultimate appetizing value and consumer acceptance towards foods and beverages. Synthetic food colours have been increasingly used than natural food colours by food manufacturers to attain certain properties such as low cost, improved appearance, high colour intensity, more colour stability, and uniformity. Varied foods and beverages available in the market may contain some nonpermitted synthetic colours and overuse of permitted synthetic colours. This may lead to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The current study revealed that 27% type of branded and 21% of unbranded selected samples (Graph 1) contained synthetic colours of some type. These findings are comparable to the findings of a study carried out at Karachi and Sri Lanka [16,25]. Summary of the dyes identified (Table 1) showed that confectionery samples consisted of approved colours ponceau 4R, carmoisine, tartrazine, sunset yellow, quinoline yellow, brilliant blue FCF.…”
Section: Spectroscopic Analysissupporting
confidence: 86%
“…The current study revealed that 27% type of branded and 21% of unbranded selected samples (Graph 1) contained synthetic colours of some type. These findings are comparable to the findings of a study carried out at Karachi and Sri Lanka [16,25]. Summary of the dyes identified (Table 1) showed that confectionery samples consisted of approved colours ponceau 4R, carmoisine, tartrazine, sunset yellow, quinoline yellow, brilliant blue FCF.…”
Section: Spectroscopic Analysissupporting
confidence: 86%
“…Food colourants are classified as artificial and natural, based on their origin. Artificial food colours are chemicals which originate from coal tar derivatives, and most of them contain an azo group (Dilrukshi et al, 2019). Considering artificial blue colours, Brilliant Blue FCF (E133, FD&C Blue No.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of society, the demand and output of pigment are on the rise. Because some synthetic pigments have toxicity, allergy, mutagenicity, carcinogenesis, and other problems, alternative healthy and harmless natural pigments are attracting more and more attention from all over the world [2]. Natural pigments mainly come from plants or microorganisms.…”
Section: Introductionmentioning
confidence: 99%